Employee Performance As Moderating For Optimizing Training And Work Discipline On Career Development - Muhammad Islah Idrus; Muhammad Ikram Idrus; Muhammad Muhammad Ismail (International Journal of Artificial Intelligence Research, 2024)
Career development is the expectation of every civil apparatus of the country. This study aims to analyze the direct influence of education and training and discipline on employee career development and when moderated by employee performance variables. This research is a study involving 115 respondents with a quantitative type of research to test hypotheses with analyst moderating (MRA) techniques. Education and training that has been carried out and prioritized by state civil servants within the scope of 11 Village Offices in Bissappu District, Bantaeng Regency has shown a good impact on career development with consideration of the optimal performance that has been implemented